2015
DOI: 10.5296/jbls.v6i2.7445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NAA and IAA on Stem Cuttings of Dalbergia Sissoo (Roxb)

Abstract: The plant cuttings is one of the most common methods of vegetative reproduction which is, today, used extensively due to low cost. In order to study the effect of various concentrations of Naphthalene acetic acid (NAA) and Indole acetic acid (IAA) on the rooting of semihardwood cuttings of Dalbergia sissoo , an experiment was carried out in a private field in Koya city in 2014. In this research, the treatments were prepared to include hormone of Naphthalene acetic acid in four levels of: (0, 100, 300 and 500 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Similarly,[28] reported that total leaf chlorophyll content in stem cuttings of three apple cultivars (Starkrimson Delicious, Golden Delicious and Misket Delicious) were significantly increased by treatment of 2000 and 3000 mg / IBA. On contrary,[29]…”
mentioning
confidence: 94%
“…Similarly,[28] reported that total leaf chlorophyll content in stem cuttings of three apple cultivars (Starkrimson Delicious, Golden Delicious and Misket Delicious) were significantly increased by treatment of 2000 and 3000 mg / IBA. On contrary,[29]…”
mentioning
confidence: 94%
“…Indirect shoot regeneration through the callus causes somaclonal variation which is not desirable for transgenic plant development (Omar and Ahmed 2015).…”
Section: Bene Ts Of Direct Shoot Regeneration Over Indirect Shoot Reg...mentioning
confidence: 99%
“…It causes prominent shoot regeneration as the endogenous level of cytokinin eradicates external supplementation. Apart from these, NAA is also increasing the internal concentration of indole-3-acetic acid (IAA) which plays an important role in shoot regeneration (Omar and Ahmed 2015). Thus, NAA-supplemented media showed prominent regeneration e ciency.…”
Section: Response Of Embryogenic Cells Of Cumin To Cytokinin and Auxinmentioning
confidence: 99%
“…Exogenous application of both rooting hormones NAA and IAA had a noticeable effect on the root and shoot parameters of Dalbergia sissoo (Omar and Khudhur, 2015). IAA is more effective than NAA on root development and growth (Ahmad, 2011).…”
Section: Introductionmentioning
confidence: 97%